After Imatinib Treatment Failure in Chronic Phase CML: What Can We Do? - Wijayanto, Nicholas; Rajabto, Wulyo (Cermin Dunia Kedokteran, 2018)
Chronic myeloid leukemia(CML) is characterized by reciprocal translocation between chromosome 9 and 22. This translocation will activate the tyrosin kinase, leads to underlying pathogenesis of CML. Imatinib is the first line of Tyrosine Kinase Inhibitor (TKI) to treat chronic phase of CML, but resistance has been a significant problem. NCCN has announced recommendation to treat imatinib resistance, including high-dose imatinib, the use of nilotinib or dasatinib.Leukemia mielositik kronik(LMK) terjadi karena translokasi resiprokal antara kromosom 9 dan 22. Translokasi ini akan mengaktifkan enzim tyrosin kinase yang mencetuskan LMK. Imatinib adalah terapi lini pertama dari golongan Tyrosin Kinase Inhibitor (TKI) untuk LMK fase kronik. Namun, resistensi terhadap imatinib menjadi masalah yang cukup signifikan. NCCN telah mengeluarkan rekomendasi untuk menangani resistensi imatinib, yaitu pemberian imatinib dosis tinggi, nilotinib atau dasatinib.